Bessel Beams and Gaussian Beams as information carriers in free space optical interconnects systems: A comparison study - Nedal k Alababneh (International Journal of Electrical and Computer Engineering (IJECE), 2019)
We introduce a comparison study for the performance of a lens-based   free space optical interconnects system assuming Bessel Beams and Gaussian Beams as information carriers.  The optical field at the detector plane was derived for the two beam profiles. In both cases the expressions for the output optical filed are expressed in terms of complex Gaussian functions. The performance of the system for the two beams is evaluated and compared. Using simulation results we show that the use of Bessel beam gives superior results to that of using Gaussian beam for large interconnects distance.